Explosive strength and endurance adaptations in young elite soccer players during two soccer seasons - Di Giminiani, R.; Visca, C. (PLOS ONE, 2017)
The purpose of the present study was to investigate the explosive strength and endurance adaptations in young elite soccer players who underwent a supervised training program for a period of two years. Nineteen players, with seven years of training experience (age: 13.3 ± 0.1 years; body weight: 57.9 ± 4.9 kg; height: 168.9 ± 4.7 cm; BMI: 20.1 ± 1.1 kg/m2), voluntarily participated in the present study. The testing sessions were performed at the beginning of the preparation period in the first (T1), second (T2), and third year (T3). The following performance variables were measured: explosive strength [squat-jump (SJ) and counter-movement-jump (CMJ)], pre-stretch augmentation (CMJ-SJ), leg stiffness [hopping test (HT)], short sprint performance [15 m (SSP15) and 30 m (SSP30)], aerobic endurance [test of Leger (VO2max)], maximal heart rate [at the last step of Leger (HR)], and speed-strength endurance [continuous counter-movement-jumps (CCMJ)]. A significant main effect on the VO2Max (+5.72%; F(2.49) = 3.822; p = 0.029; ES = 1.00), HR (-1.70%; F(2.54) = 3.472; p = 0.038; ES = 0.97), CCMJ (+7.64%; F(2.54) = 5.438; p = 0.007; ES = 1.15), SJ (+10.26%; F(2.54) = 15.254; p = 0.0001; ES = 1.53), CMJ (+7.36; F(2.54) = 8.270; p = 0.001; ES = 1.33), HT (+8.34%; F(2.48) = 3.297; p = 0.046; ES = 1.01), SSP15 (-3.50%; F(2.44) = 12.760; p = 0.0001; ES = 1.53), and SSP30 (-4.44%; F(2.44) = 5.797; p = 0.006; ES = 1.16) was observed in the two soccer seasons. These results highlight that, in long-term training, the monitoring of the adaptive responses in relation to the training load may provide a guideline to optimize the trainability of some performance variables in young elite soccer players (13-15 years). In the present study, we cannot exclude the influence of growth and maturation on some performance variables; therefore, the monitored adaptive responses should be considered as the possible results of an interaction between the applied training load and maturation.